PENGARUH TERAPI TERTAWA TERHADAP TEKANAN DARAH LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS RASIMAH AHMAD KOTA - Fitrina, Yossi; Bungsu, Pera Putra; Pramestika, Ririn (Jurnal Kesehatan Saintika Meditory, 2023)
Hypertension or high blood pressure is a condition in which an increase in blood pressure cancauseblockage of blood flow and can be prevented by non-pharmacological management, namely relaxationwith laughter therapy. The purpose of this study to see the effect of laughtertherapy on the bloodpressure of elderly with hypertension in the working area of the RasimahAhmad Public Health Center,Bukittinggi City 2022. This type of research was Quasy Experimental, namely one group pre-post testdesign. The sampling technique used in this study is non-probability sampling (purposive sampling).The study was conducted from March 2022at the Rasimah Ahmad Health Center with 16 samples.This study used experimental methods,the data analyzed by univariate and bivariate. The results of theanalysis showed that there was an effect of laughter therapy on the blood pressure of the elderly withhypertension in theWork Area of the Rasimah Ahmad Health Center in 2022. This research can beused as complementary therapy for hypertension patient that can be used by society.Keywords: Hypertension, Elderly, Blood Pressure, Humor Therapy, Laughter Therapy